Assessment of Elements of Abuse of Authority (Detournement De Pouvoir) Based on the Decision of the Constitutional Court: Penilaian Unsur Penyalahgunaan Wewenang (Detournement De Pouvoir) Berdasarkan Putusan Mahkamah konstitusi - Titon Slamet Kurnia (Jurnal Konstitusi, 2023)
Detournement de pouvoir was regulated in administrative and criminal law. However, the assessment of it was often confused. Therefore, the Constitutional Court through Decision 25/PUU-XIV/2016 provides a line of demarcation in assessing the element of Detournement de pouvoir that must be handled under administrative and criminal law. This article tries to explain the ratio decidendie of the constitutional court through a series of identifications of Detournement de pouvoir. This article uses a statutory approach and presents two main findings; First, the assessment of detournement de pouvoir must be understood based on tort of two field of law. Second, abuse of authority is included as tort in administrative law as long as it relates dwaling of authority, procedures/conditions and substance of the exercise of authority, while abuse of authority can be included as tort in criminal law as long as it contains of dwal badrog, namely bribery, coercion and deception.